Preparation of Divergent Intermediates and Convergent Synthesis of Phytofluene - Boo, Chanyoung; Kim, Hyein; Yang, Huijeong; Han, Seunghyo; Yeo, Huisu; Seo, Chibeom; Koo, Sangho (Synthesis, 2023)
Practical synthetic methods for biogenetically and pharmaceutically important phytofluene were developed through the divergent preparation of key C20 substrates from a common intermediate and convergent synthesis by Wittig and Julia–Kocienski olefinations. Expeditious synthesis of phytofluene was also proposed based on the Julia sulfone-mediated chain-extension and double elimination method. Stereochemical outcomes of these olefination methods for phytofluene were compared and the Julia–Kocienski method was the mildest and most efficient reaction condition to produce all-(E)-phytofluene. Complete 1H and 13C NMR analysis of all-(E)-phytofluene is reported for the first time. Phytofluene undergoes facile thermal isomerization to other Z-isomers above room temperature, which was also confirmed with a C30 phytofluene homologue.
Keywords: carotenoids; isomerization; olefination; phytofluene; sulfones; total synthesis